Allicin up-regulates cellular glutathione level in vascular endothelial cells. - Horev-Azaria L; Eliav S; Izigov N; Pri-Chen S; Mirelman D; Miron T; Rabinkov A; Wilchek M; Jacob-Hirsch J; Amariglio N; Savion N (European Journal of Nutrition, 2009)
BACKGROUND: Allicin in garlic is the primary active compound known to rapidly interact with free thiols. AIMS OF THE STUDY: To examine the effect of allicin on gene expression and glutathione cellular level in vascular endothelial cells. METHODS: Cultured endothelial cells were exposed to allicin; mRNA was prepared and subjected to Micro-array and Real-Time PCR. Glutathione cellular level was determined on cell lysates. RESULTS: Micro-array analysis demonstrated allicin-induced up- and down-regulation of 116 and 100 genes, respectively. Up-regulated genes included the phase II detoxifying enzymes thioredoxin reductase 1 and 2, heme oxygenase-1 and glutamate cysteine lygaze modifier subunit, the rate limiting enzyme in glutathione biosynthesis. Endothelial cells exposed to allicin and its derivatives containing glutathione or cysteine residues increased cellular glutathione. Allicin increased the glutathione level in a concentration and time-dependent manner up to 8-fold at a concentration of 10-20 microM after 28 h exposure. Furthermore, allicin derivative-treated cultures demonstrated a 50% decrease in tBuOOH cytotoxicity. CONCLUSIONS: These results may suggest a putative role for allicin and its derivatives in preventing reactive oxygen species damage by up-regulating the phase II detoxifying enzymes and increasing the cellular glutathione level.